Gujarati Text Localization, Extraction and Binarization from Images - Patel, J. M; Desai, A. A (International Journal of Computer Sciences and Engineering, 2025)
In this paper, first ever attempt to automatic detection and extraction of Gujarati text from image has been presented. This method is based on Haar discrete wavelet transform (HDWT), edge detection and connected component analysis. The distinct features of Gujarati script make it hard to directly apply the existing text detection methods designed for English, Chinese and other languages. In proposed work, first high-frequency wavelet coefficients are extracted using HDWT and then sobel filter is applied on to detect candidate text edges. Then connected component analysis is performed using area geometric feature to get rid of non-text area. The proposed method is tested on a variety of images such as images of complex background and images of different fonts, colour, and size of text. The experiment on over 878 images show that the proposed method can detect regions and isolation of text perfectly including modifier. The proposed framework has achieved a precision of 0.91, recall of 0.97 and f measure of 0.94